Enterprise metadata - Timofeeva, Irina (2022)
This master’s thesis is focused on the task of managing enterprise data and metadata. The main goal of the thesis is to find a way to make working with data and metadata more convenient and faster for employees of the AllGames company. The theoretical part introduces terms such as data, data models and data quality. After that, the issue of metadata definition is presented, as well as metadata contexts and types. In the next theoretical chapter, Jobs-to-be-Done theory is described. The chapter also describes JTBD core tenets and principles. In the practical part, the AllGames company is introduced. Information about the company is discussed such as the current situation with data and metadata, the understanding of metadata, metadata structure. The current solution used in the company is also presented. Jobs-to-be-Done research was conducted to determine what should be done to improve the user experience when working with data. Then the final JTBD matrix was created based on insights from the research. In the end, requirements for the new version of the tool were created based on the JTBD research. The main benefit of the work is the practical application of the acquired theoretical knowledge to existing problems related to working with data in a real company.